Optimizing The Role of Immigration Civil Servant Investigator in Treating Criminal Actions of People Smuggling - Doniar Andre Vernanda; Tony Mirwanto (Polteknik Imigrasi, 2020)
Immigration law enforcement is carried out by civil servant investigators (PPNS) of Immigration by the mandate of Law No. 6 of 2011 on immigration. Immigration civil servant investigators have the authority to carry out the investigation process to hand over case files for subsequent prosecution in court by the public prosecutor. The results and discussion of this research are: (i) People smuggling is a crime where people illegally enter humans without legal and valid immigration travel documents aimed at personal or group gain by entering a country without going through an examination. immigration at the immigration checkpoint (TPI). Criminal sanctions related to human smuggling are regulated in article 120 of the Immigration Law with a maximum threat of 15 years and a fine of Rp. 1,500,000,000.00. (ii) According to the Immigration Law, pro Justitia law enforcement in immigration crimes is carried out by immigration civil servant investigators who have the duties and functions of carrying out investigations & investigations, coordinating with the National Police and other law enforcement agencies as well as carrying out other matters which are ordered by immigration Law